2001
DOI: 10.1046/j.1460-9592.2001.01459.x
|View full text |Cite
|
Sign up to set email alerts
|

Myocardium Extending from the Left Atrium onto the Pulmonary Veins: A Comparison Between Subjects with and Without Atrial Fibrillation

Abstract: Rapid discharges from the myocardium extendingfrom the left atrium onto the pulmonary vein (PV) have been shown to initiate AF, and AF may be eradicated by the catheter ablation within the PV. However, if there is any difference in the distribution patterns of the myocardial sleeve onto the PV between the subjects with and without AF is to be determined. Twenty-one autopsied hearts were examined. Eleven patients previously had AF before death and another 10 patients had normal sinus rhythm as confirmed from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
61
3
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 9 publications
7
61
3
2
Order By: Relevance
“…The degree of extension of myocardium was the longest in the superior left PV and the shortest in the right inferior PV (4). The extension of myocardium onto the PVs determined by us was highly correlated with the frequency of foci within PV as reported by other workers (4,5). However, the histology of the myocardium on the PVs showed no difference between the AF and non-AF patients.…”
Section: Myocardium Extending Onto Pvssupporting
confidence: 88%
“…The degree of extension of myocardium was the longest in the superior left PV and the shortest in the right inferior PV (4). The extension of myocardium onto the PVs determined by us was highly correlated with the frequency of foci within PV as reported by other workers (4,5). However, the histology of the myocardium on the PVs showed no difference between the AF and non-AF patients.…”
Section: Myocardium Extending Onto Pvssupporting
confidence: 88%
“…Furthermore, it has been shown that an electrical connection of the PV musculature and left atrial muscle may be more fixed in patients with AF than in those without, [7][8][9] while there is sometimes no myocardial extension into PVs in the patients without a history of AF.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Steiner et al (2006) reported that amyloid deposition and scarring in myocardial sleeves t e n d e d t o b e o b s e r v e d m o r e f r e q u e n t l y i n AF patients relative to control patients. Interestingly, the incidence of atrial myocardium extending beyond the PV-LA junction up to the PV periphery in all the examined PV specimens is commonly reported to be 88 to 89% (Tagawa et al, 2001;Steiner et al, 2006).…”
Section: Myocardial Sleeves In Pvmentioning
confidence: 93%
“…Importance of the myocardial sleeves as arrhythmogenic foci in AF is confirmed also in the human postmortem studies. Tagawa et al (2001) investigated myocardial sleeve distribution in patients with AF or without AF. They showed that the significantly longer distance of sleeves extending to the peripheral end of PV in AF patients relative to the distance in control patients was confirmed in inferior but not superior PV.…”
Section: Myocardial Sleeves In Pvmentioning
confidence: 99%